Nilai-nilai Pendidikan Karakter Tema Hidup Rukun pada Buku Siswa di Sekolah Dasar - Khairani, Annisa; Ain, Siti Quratul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to analyze and describe the character values ​​contained in the 2013 curriculum integrative thematic book published by the Ministry of Education and Culture. The data and data sources in this study are the second-grade students' books with the theme